Redundancy among phospholipase D isoforms in resistance triggered by recognition of the Pseudomonas syringae effector AvrRpm1 in Arabidopsis thaliana - Johansson, Oskar N.; Fahlberg, Per; Karimi, Elham; Nilsson, Anders K.; Ellerström, Mats; Andersson, Mats X. (Frontiers in Plant Science, 2014)
Plants possess a highly sophisticated system for defense against microorganisms. So called MAMP (Microbe Associated Molecular Patterns) triggered immunity (MTI) prevents the majority of non-adapted pathogens from causing disease. Adapted plant pathogens use secreted effector proteins to interfere with such signaling. Recognition of microbial effectors or their activity by plant resistance (R)-proteins triggers a second line of defense resulting in effector triggered immunity (ETI). The latter usually comprises the hypersensitive response (HR) which includes programmed cell death at the site of infection. Phospholipase D (PLD) mediated production of phosphatidic acid (PA) has been linked to both MTI and ETI in plants. Inhibition of PLD activity has been shown to attenuate MTI as well as ETI. In this study, we systematically tested single and double knockouts in all 12 genes encoding PLDs in Arabidopsis thaliana for effects on ETI and MTI. No single PLD could be linked to ETI triggered by recognition of effectors secreted by the bacterium Pseudomonas syringae. However, repression of PLD dependent PA production by n-butanol strongly inhibited the HR following P. syringae effector recognition. In addition some pld mutants were more sensitive to n-butanol than wild type. Thus, the effect of mutations of PLDs could become detectable, and the corresponding genes can be proposed to be involved in the HR. Only knockout of PLDδ caused a loss of MTI-induced cell wall based defense against the non-host powdery mildew Erysiphe pisi. This is thus in stark contrast to the involvement of a multitude of PLD isoforms in the HR triggered by AvrRpm1 recognition.